Degree achievements. Um estudo comparativo entre português europeu e inglês - Ferreira, Inês (elingUP: Revista Eletrónica de Linguística dos Estudantes da Universidade do Porto, 2018)
Degree Achievements (DAs) are constructions projected by deadjectival verbs, and present the feature of an ambiguous reading, that goes from telic to atelic. Since they derive from gradual adjectives, the Degree Achievements are, themselves, associated to two types of scale – open and closed – that they inhertit from the adjetives they derive from. In the present paper, our goal is to make a comparison between DAs in two different languages, European Portuguese and English, especially concerning the telicity parameter.